Covert Sarong Culture Education policy - Amang Fathurrohman (STAI Miftahul Ula Nganjuk, 2019)
The policy in the governance of Islamic education in Indonesia between the Ministry of Education and Culture which is decentralized and the Ministry of religious which is centralized impact on the quality, service, and support is also different. Islamic Educational institutions managed by the Ministry of Religious Affairs although in each region have grown rapidly, but the local government tends not to support the full in Islamic education services because it is not their obligation. This study uses qualitative research methods with political research approaches in institutional perspectives. Sources of research are taken from education policymakers and stakeholders in Pasuruan Regency. Data collection is using document review, observation, and in-depth interviews. Data analysis is using interactive models A. Michael Huberman and Mattew B. Miles. Check data validation is through transferability, dependability, and confirmability.This article will reveal the efforts of the Pasuruan Regency Government to integrate the education governance in the Quranic read-write program. The results of this research showed that with regional autonomy, the government of Pasuruan Regency initiated the education policy